Self-Presentation and Adolescent Altruistic Behaviors in Social Networks - Yaling Zhu; Yue Shen; Qiang Zhao (Complexity)
Social networks provide a convenient place for people to interact; members in social networks may create new connections or break existing connections, driving the evolution of complex network structure. Dynamics in social networks, such as opinion formation and spreading dynamics, may result in complex collective phenomena. This paper conducts a survey on 495 students from six schools in Shaanxi, Henan, and Zhejiang provinces and discusses the impact of self-presentation on adolescent network altruistic behaviors, the intermediary role of social ability cognition, and the moderating role of privacy awareness. The results show the following: (1) Self-presentation in social networks can positively predict adolescent network altruistic behaviors. The positive prediction effect of network sharing is the largest, and the positive prediction effect of network support is the least. (2) Social ability cognition plays an intermediary role between self-presentation and adolescent network altruistic behaviors. (3) The moderating effect of privacy awareness is not significant.